Assessing Community Attitudes Towards Home-Based Male Caregivers for Daycare Children - Adedokun, Theophilus Adedayo; Adedokun, Elizabeth Temilade (Indonesian Journal of Early Childhood Education Studies, 2023)
This study explored community attitudes toward home-based male caregivers for daycare children in Ogbomoso, Nigeria. The aim was to understand perspectives on using male versus female caregivers. Respondents included equal numbers of married men and women aged 30-50 years old. The study asked about their willingness to use male caregivers, reasons behind their decision, expected impacts on children, and need for societal change. The study took place in Ogbomoso South and North Local Government of Nigeria, where 32 parents and prospective parents were surveyed about their attitudes toward home-based male caregivers for daycare children. A qualitative approach was used, with accidental sampling. Inductive thematic analysis elicited key themes shaping attitudes and norms. A prevalent theme was associating caregiving with inherent female capabilities and maternal duties - many felt women naturally provide superior nurturing and care while men lack these innate aptitudes. Alongside this was strong distrust of males with children, stemming from abuse and misconduct fears. However, some felt gender irrelevant, professing egalitarian ideals. But pursuing equality conflicted with lingering scepticism about men's care motivations. It's apparent that parents lack a framework for choosing caregivers yet choose for their children. Such a framework could help bridge the gender inequality gap in caregiving.